2020
DOI: 10.21595/vp.2020.21509
|View full text |Cite
|
Sign up to set email alerts
|

Slow oscillations in systems with inertial vibration exciters

Abstract: The problem of the occurrence of semi-slow speed oscillations of an unbalanced rotor during its passage through the resonance zone has been solved using the method of direct separation of motions. It has been proved that when a stationary regime is established, semi-slow damping oscillations of the rotor speed arise in the region of the Sommerfeld effect, they are the result of the superimposement of free accompanying oscillations with a relatively low frequency on forced fast oscillations. In this respect, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…- [5] -for a pendulum rigidly mounted on the shaft of an induction electric motor installed on a platform that fluctuates horizontally.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…- [5] -for a pendulum rigidly mounted on the shaft of an induction electric motor installed on a platform that fluctuates horizontally.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The studies reported in [3][4][5] found that unbalanced masses (pendulums, wind wheels, etc.) get stuck at one of the resonant frequencies of platform oscillations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The easiest technique to excite resonant vibrations in vibratory machines is based on the Sommerfeld effect [7]. There are examples of this technique's application for singlemass [8], two-mass [9,10], and three-mass [11] vibratory machines. The effect is manifested in that the unbalanced rotor of a DC electric motor [9], or induction motor [8,10], the unbalanced impeller [11] cannot accelerate to the working frequency and gets stuck at one of the resonant frequencies of platform vibrations.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Vibratory machines can be single-and multi-mass. It should be noted that multi-mass vibratory machines possess a series of advantages over single-mass ones [3][4][5][6][7][8][9][10][11]. Thus, a multi-mass structure makes it possible to design vibratory machines that almost do not transmit vibrations to the foundation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation